Вплив купрум сульфату водного середовища на частоту серцебиття перлівницевих (Mollusca, Bivalvia, Unionidae) - Стадниченко, Агнеса; Вискушенко, Дмитро; Stadnychenko, Agnessa; Vyskushenko, Dmytro (Східноєвропейський національний університет імені Лесі Українки, 2015)
Розглянуто вплив різних концентрацій (0,1, 1, 10 мг/дм3 ) купрум сульфату водного середовища на частоту серцебиття трьох видів перлівницевих. З’ясовано, що за 0,1 мг/дм3 токсиканту у всіх досліджених молюсків ритм серцевих скорочень прискорюється. Зі збільшенням концентрації купрум сульфату у воді до 1, а потім до 10 мг/дм3 у цих тварин розвивається прогресуюча брадикардія. The article focuses on the influence of the different concentrations (0,1, 1, 10 mg/dm3 ) cuprum sulfate of water environment on physiological state of Unio conus, U. rostratus, Colletopterum piscinale – the most widespred and numerous species from unionides in Ukraine. The heart beat frequency obtain visually from the fistulary animals have been used as the test-function. In solution which contain 0,1 mg/dm3 cuprum sulfate heart beat frequency sharply raisees in all reserched species. It is one from the protective compensatory adaptation correspond to the phase stimulation of poisoning process. With cuprum sulfate concentrations increase to 1 mg/dm3 bradycardia becomes evident in these animals. It sharply progresses if cuprum sulfate concentration increase to 10 mg/dm3 . With 1 mg/dm3 cuprum sulfate physiological state of unionides corresnond to depressive phase of poisoning process. With 10 mg/dm3 this matter in environment result in the rapid go after of two last phases of poisoning process – sublethal and lethal. These unionides maybe use in the ecological monitoring system as species-indicators.
The Influence of Cuprum Sulphate of Water Environment on Unionides (Mollusca, Bivalvia, Unionidae) Heart Beat Frequency
Keywords: перлівницеві; купрум сульфат; частота серцебиття; unionides; cuprum sulphate; heart rhythm